Prevalence of umbilical artery Doppler waveform abnormality during the early second trimester and the subsequent variation of waveforms in monochorionic diamniotic twin pregnancies: A prospective cohort study. Issue 7 (25th April 2021) - Nakanishi, Kentaro; Muto, Haruka; Yamamoto, Ryo; Kawaguchi, Haruna; Hayashi, Shusaku; Ishii, Keisuke
Abstract: Aim: To investigate the prevalence of qualitative abnormal umbilical artery Doppler waveforms (Abnormal UA) during the early second trimester and the subsequent variation of waveforms in monochorionic diamniotic (MCDA) twin pregnancies. Methods: This prospective cohort study included 153 MCDA twin pregnancies. Pulsed Doppler examinations for UA were performed at four points, including the free‐loop (FL) and near the placental cord insertion site (CI) of each UA, between 16 and 17 weeks' gestation. Cases were classified into positive diastolic waveforms (Type I), persistent Abnormal UA (Type II), and intermittent Abnormal UA (Type III). When the diastolic velocity in UA Doppler was positive twice after different sequential recordings, the cases were determined to have achieved normalization. Follow‐up Doppler examinations of the UA were performed at 24, 28, and 32 weeks' gestation. Results: Of all 153 cases, 38 (25%; 19 Type II and 19 Type III cases) showed Abnormal UA at the first examination. Abnormal UA was detectable at FL in all selective intrauterine growth restriction (sIUGR) cases, whereas it was noted only at CI site in some non‐sIUGR cases. Abnormal UA normalized in 12 (63%) Type II and 15 (79%) Type III cases. Conclusions: A quarter of MCDA twin pregnancies in the early second trimester demonstrated Abnormal UA. In MCDA twins with Abnormal UA between 16 and 17 weeks' gestation, it is preferable to follow them up to consider the possibility of normalization of Abnormal UA as well as features of UA waveforms specific to FL and CI.